2016
DOI: 10.1038/nrn.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Integrating neuroimmune systems in the neurobiology of depression

Abstract: Data from clinical and preclinical studies indicate that immune dysregulation, specifically of inflammatory processes, is associated with symptoms of major depressive disorder (MDD). In particular, increased levels of circulating pro-inflammatory cytokines and concomitant activation of brain-resident microglia can lead to depressive behavioural symptoms. Repeated exposure to psychological stress has a profound impact on peripheral immune responses and perturbs the function of brain microglia, which may contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
403
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(421 citation statements)
references
References 226 publications
13
403
0
5
Order By: Relevance
“…Unfortunately, current main antidepressants, such as selective serotonin reuptake inhibitors (SSRIs) and tricyclic anti-depressants (TCAs), display unsatisfactory response rates and various side effects [2]. Although the etiology and pathophysiology of depression remain unknown, recent evidence suggests that inflammation can affect the brain and play a vital role in the psychopathology of depression [3, 4]. The previous reports from our and other laboratories have identified the underlying role of several endogenous alarmins or damage-associated molecular patterns (DAMPs), such as high mobility group box 1 (HMGB1) [5–7] and adenosine triphosphate (ATP) [8], in neuroinflammation and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, current main antidepressants, such as selective serotonin reuptake inhibitors (SSRIs) and tricyclic anti-depressants (TCAs), display unsatisfactory response rates and various side effects [2]. Although the etiology and pathophysiology of depression remain unknown, recent evidence suggests that inflammation can affect the brain and play a vital role in the psychopathology of depression [3, 4]. The previous reports from our and other laboratories have identified the underlying role of several endogenous alarmins or damage-associated molecular patterns (DAMPs), such as high mobility group box 1 (HMGB1) [5–7] and adenosine triphosphate (ATP) [8], in neuroinflammation and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of primary hippocampal neurons have shown that TNF signaling controls synaptic scaling by increasing trafficking of AMPA glutamate receptors and decreasing the numbers of surface GABA receptors (Wohleb et al, 2016). Experimental application of TNF to hippocampal slices induced a rapid increase in excitatory postsynaptic electrical activity mediated by increased expression of overactive surface AMPA receptors (Beattie et al, 2002) associated with an overrepresentation of GluA1compared with GluA2subu-nits (Vezzani and Viviani, 2015).…”
Section: Tnfmentioning
confidence: 99%
“…Furthermore, a CTNNA2 SNP was associated with BD in a GWAS study [58]. IL34 is a cytokine that is implicated in immune response and might play an important role in inflammatory mechanisms in mood disorders [59,60]. For instance, IL34 cytokine is important for the survival of microglia, the macrophages of the brain that determine the levels of inflammation in the cellular environments [61].…”
Section: Discussionmentioning
confidence: 99%